Integrated strategies for effective remediation of chromium-contaminated soils: Advancements, challenges, and sustainability implications - Yingying Xing; Yu Zheng; Xiukang Wang (Environmental Advances)
Soil chromium contamination represents a significant global environmental challenge, posing serious risks to human health and ecosystems. The toxicity of hexavalent chromium, in particular, underscores the need for effective remediation strategies to mitigate its harmful effects. This review aims to evaluate various remediation methods for chromium-contaminated soils, including engineering, bioremediation, chemical, and agricultural approaches. It synthesizes existing literature to identify advancements and challenges associated with each method, focusing on their effectiveness, duration, and environmental impact. The findings indicate that solidification/stabilization techniques are effective in sequestering chromium; however, they raise concerns regarding long-term stability. Bioremediation, which employs hyperaccumulator plants and specific microorganisms, shows promise in reducing hexavalent chromium to its less toxic trivalent form, although it is often constrained by prolonged remediation times. Chemical methods, while effective, encounter challenges related to dosage control and the management of secondary pollutants. Agricultural strategies, including optimized land use and fertilization practices, can help mitigate chromium pollution but require careful management to enhance their efficacy. This review highlights the importance of integrating multiple remediation techniques to achieve optimal results. It emphasizes the potential of eco-friendly methods such as phytoremediation and constructed wetlands, which not only remove pollutants but also improve soil quality. Additionally, the study underscores the necessity of incorporating economic and environmental sustainability assessments into the development of comprehensive remediation strategies. The review concludes that an integrated approach combining engineering, bioremediation, chemical, and agricultural methods is essential for effectively managing chromium contamination in soils. By promoting sustainable practices in soil management and environmental protection, these strategies contribute to the broader goals of pollution prevention and ecological restoration, aligning with national development objectives and enhancing public health and safety.